2022
DOI: 10.1055/s-0042-1757261
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Placenta Accreta Spectrum Severity and Incidence of Small for Gestational Age Neonates

Abstract: Objective The aim of the study is to evaluate whether pathologic severity of placenta accreta spectrum (PAS) is correlated with the incidence of small for gestational age (SGA) and neonatal birthweight. Study Design This was a multicenter cohort study of viable, non-anomalous, singleton gestations delivered with histology-proven PAS. Data including maternal history, neonatal birthweight, and placental pathology were collected and deidentified. Pathology was defined as accreta, increta, or percreta.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…[18,19,22] The potential linkage of SGA may lie in the placental pathology per se, as previous studies suggested that both PP and PAS can contribute to SGA or intra-uterine growth restriction due to impaired uteroplacental circulation. [40][41][42] Yet, it is noteworthy that not all adverse neonatal outcomes in the ECD groups are solely attributed to the lower gestational age at delivery. A recent multinational, multicenter cohort study based on the International Society for Placenta Accreta Spectrum (IS-PAS) registry compared neonatal outcomes between different modes of cesarean delivery within the same gestational range (24 0/7 -34 0/7 weeks, 34 1/7 -36 0/7 weeks, and 36 1/7 weeks).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18,19,22] The potential linkage of SGA may lie in the placental pathology per se, as previous studies suggested that both PP and PAS can contribute to SGA or intra-uterine growth restriction due to impaired uteroplacental circulation. [40][41][42] Yet, it is noteworthy that not all adverse neonatal outcomes in the ECD groups are solely attributed to the lower gestational age at delivery. A recent multinational, multicenter cohort study based on the International Society for Placenta Accreta Spectrum (IS-PAS) registry compared neonatal outcomes between different modes of cesarean delivery within the same gestational range (24 0/7 -34 0/7 weeks, 34 1/7 -36 0/7 weeks, and 36 1/7 weeks).…”
Section: Discussionmentioning
confidence: 99%
“…[18,19,22] The potential linkage of SGA may lie in the placental pathology per se, as previous studies suggested that both PP and PAS can contribute to SGA or intra-uterine growth restriction due to impaired uteroplacental circulation. [40–42]…”
Section: Discussionmentioning
confidence: 99%